سياسة مكافحة الفساد الاداري في الجزائر - شهيرة بن النية (جامعة المسيلة, 2020)
ملخص الدراسة باللغة العربية تتناول هذه الدراسة وتهتم بتشخيص ظاهرة الفساد الإداري في الجزائر، وذلك بالتعرف على ماهيته ومظاهره وأسبابه وآثاره، فتشخيص المشكلة هي أولى مراحل المكافحة، كما تضمنت الدراسة الإستراتيجية التي تبنتها الجزائر في مكافحتها للفساد الإداري. أما إشكالية الدراسة فتمحورت حول: ماهي السياسة التي انتهجتها الجزائر لمكافحة الفساد الإداري؟ ويسعى هذا الموضوع إلى الكشف عن السياسة الجزائرية المعتمدة لمحاربة الفساد ومدى فعاليتها، والتي كانت مزيجا ما بين الآليات التشريعية المؤسسية وآليات الإصلاح الإداري، وكذا تفعيل دور المجتمع المدني والإعلام للحد من شبح ظاهرة الفساد الإداري. ملخص الدراسة باللغة الإنجليزية: This study deals with and is interested in diagnosing the phenomenon of administrative corruption in Algeria, by identifying its nature, manifestations, causes and effects, so the diagnosis of the problem is the first stage of control. as the strategic study that Algeria adopted in its fight against administrative corruption included. As for the problem of the study, it focused on: What is the policy adopted by Algeria to combat administrative corruption? This topic seeks to reveal the Algerian policy adopted to combat corruption and its effectiveness, which was a mix between institutional legislative mechanisms and mechanisms for administrative reform, as well as activating civil society and the media to reduce the specter of administrative corruption.
Keywords: مكافحة الفساد -الاداري - الجزائر